Oropharyngeal Seal, the Primary Mechanism Involved in Maintaining the Soft Palate in a Ventral Position Within the Nasopharynx of Equids: Its Role in Maintaining a Horse’s Health and Well-Being, along with Surgical Approaches that Could Potentially Enhance Its Function. - Ahern, Tom (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The notion of an oral seal mechanism arose in an attempt to explain the rational behind a newly developed surgical procedure, an oral palatopharyngoplasty. This theory was further refined and described after viewing numerous treadmill recordings. Eventually its role in maintaining a patent nasopharyngeal airway was established and the term palatal instability was introduced. A critical review of the role or efficacy of surgical procedures, many of which were not originally designed to treat this condition was needed. Likewise the interrelationship between this mechanical dysfunction and other airways issues within the larynx and nasopharynx, along with the health of the lower airways in general, and a possible role in maintaining airway patency during paradoxical sleep, were in urgent need of investigation.